The Difficulties of Subtitling Yemeni Arabic Effective Similes into English - Ali Mohammed Saleh Mohammed Saleh Al-Hamzi (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2025)
Audiovisual translation is a significant element of media consumption worldwide, particularly for non-native speakers. Subtitling is predominant in audiovisual translation across the Arab region; however, there are only a few training schools and universities that can adequately prepare subtitlers for entry into the industry. The present study seeks to identify a major difficulty Arabic-speaking subtitlers encounter when translating effective simile phrases from colloquial Arabic to English. The study examines the strategies pursued by ten MA candidates in the MA in Audiovisual Translation at Sana’a University in their handling of Arabic effective similes during subtitling exercises. The study found that four primary strategies are pursued by MA candidates: converting an effective simile into sense, reproducing a similar image in the target language, substituting the source-language image with a conventional target-language image, and pursuing a literal translation. The study identifies a greater need for enhanced pedagogy and subtitling training in the Arab region to address such challenges and improve subtitling quality. The researcher recommends increased exposure to audiovisual materials with complex simile phrases during training, as well as encouraging students to study and read pertinent works on the subject to become professional subtitlers with a solid academic foundation